(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Record linkage - i.e. the use and linkage of electronic, mainly administrative databases - has been utilized in epidemiologic research for over three decades now, starting from the system implemented in a few US health maintenance organizations (HMO, i.e. the Kaiser Permanente network), a few Nordic countries systems, or the UK general practice research database (UK GPRD, now clinical practice research datalink, CPRD) [1, 2]...